1995
DOI: 10.1039/c39950000533
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis of CH4 at a TiO2 surface from gaseous H2O and CO2

Abstract: UV irradiation of the gadsolid interface of microcrystalline Ti02 in the presence of water and carbon dioxide in the gas phase at 343 K leads to photoreduction of carbon dioxide to form carbon monoxide, hydrogen and methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 4 publications
5
27
0
2
Order By: Relevance
“…The appearance of the heavier alcohols at or above 150°C is consistent with an FTS-like mechanism becoming active as the thermal energy approaches the activation energy needed for chain formation (37,38,40). In a related study of the effect of temperature on the photochemical reduction of CO 2 to methane over TiO 2 , Saladin et al showed that the rate of methane formation increases upon going from 20 to 200°C, indicating the rate-determining step is a thermal process (41,42). Significantly, no higher C n products were reported, which we suspect is because they lacked a proper FTS cocatalyst, such as cobalt.…”
Section: Resultsmentioning
confidence: 78%
“…The appearance of the heavier alcohols at or above 150°C is consistent with an FTS-like mechanism becoming active as the thermal energy approaches the activation energy needed for chain formation (37,38,40). In a related study of the effect of temperature on the photochemical reduction of CO 2 to methane over TiO 2 , Saladin et al showed that the rate of methane formation increases upon going from 20 to 200°C, indicating the rate-determining step is a thermal process (41,42). Significantly, no higher C n products were reported, which we suspect is because they lacked a proper FTS cocatalyst, such as cobalt.…”
Section: Resultsmentioning
confidence: 78%
“…[17][18][19][20][21][22] The co-adsorption of CO 2 and H 2 O on rutile (110) have been studied by both experiments and theory. 19,[23][24][25][26][27][28][29][30][31] In the experiment, the co-adsorption behavior of CO 2 and H 2 O under UHV conditions were examined by Henderson.…”
mentioning
confidence: 99%
“…The photocatalytic reduction of CO 2 on TiO 2 has been studied in aqueous solutions [4,[6][7][8][9][10][11][12][13], in liquid CO 2 [14] and in solid-gas systems [15][16][17][18]. The efficiency of the conversion of CO 2 to fuels in aqueous suspension systems was very low when H 2 O was used as the reductant but higher yields of products were obtained in the presence of molecules acting as hole sacrificial scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…The formation rate of methane was much enhanced in the presence of 2-propanol [8,14] but the presence of organic molecules can interfere with the detection of the CO 2 reduction products so that the reaction of CO 2 with H 2 O vapour is a more desirable system. Saladin et al [16] obtained CO, H 2 and CH 4 by UV irradiation of microcrystalline TiO 2 powder in the presence of CO 2 and H 2 O in gas phase. Anpo et al [15] found CH 4 as the major product produced on anatase TiO 2 powders.…”
Section: Introductionmentioning
confidence: 99%